Hippocampus and Prefrontal Cortex Predict Distinct Timescales of Activation in the Human Ventral Tegmental Area. (29th January 2016) - Murty, Vishnu P.; Ballard, Ian C.; Adcock, R. Alison
Abstract: The mesolimbic dopamine system contributes to a remarkable variety of behaviors at multiple timescales. Midbrain neurons have fast and slow signaling components, and specific afferent systems, such as the hippocampus (HPC) and prefrontal cortex (PFC), have been demonstrated to drive these components in anesthetized animals. Whether these interactions exist during behavior, however, is unknown. To address this question, we developed a novel analysis of human functional magnetic resonance imaging data that fits models of network excitation and inhibition on ventral tegmental area (VTA) activation. We show that specific afferent systems predict distinct temporal components of midbrain VTA signal. We found that PFC, but not HPC, positively predicted transient, event-evoked VTA activation. In contrast, HPC, but not PFC, positively predicted slow shifts in VTA baseline variability. Thus, unique functional contributions of afferent systems to VTA physiology are detectable at the network level in behaving humans. The findings support models of dopamine function in which dissociable neural circuits support different aspects of motivated behavior via active regulation of tonic and phasic signals.